Experimenting from the Archive: a Situated Reflection in Architecture - Vargas Hidalgo, Jose (2026)
The objective of this paper is to evaluate how archives have become tools and inputs for the architectural production, in particular, for one interested in combining practices within history and theory of architecture along with design practices. Therefore, this discussion sequentially examines the relationship between archives and Architecture by reviewing concepts, case studies, and drawing on teaching experience at the School of Architecture, University of Costa Rica. As a conclusion, it is determined that archives allow for experimental attitudes towards Architecture, particularly when studying the past, not to replicate or copy it, but to find speculative conditions about its present and future.